Comunicação da informação em redes virtuais de aprendizagem - Freire, Gustavo Henrique de Araújo (2004)
Contemporary society is based on two pillars: information and knowledge, supported by digital technologies. It brings the necessity of a new attitude and the acquisition of new skills by the users, mainly in the process of communicating the information. This new attitudes and skills result in a search for continuous learning and in the use of intellectual technologies. This process occurs in every single level of contemporary society, involving activities such as training and capability improvement and, mainly, production and management of information. In this sense, learning virtual networks are fundamental to facilitate the communication of information in a society whose structure is becoming more and more distant of hierarchy. This digital network is presented in a new channel of communication of information: the cyberspace. In this process, professors and professionals of information are seen as facilitation agents; on the other side, in learning virtual networks, a professional of information can also be a manager of virtual environment